Alternate Universe (AU) Vs. Kreativitas Menulis Gen Z pada Tren Digitalisasi Sastra - Ni Putu Intan Permatasari; Dwi Oktaviani (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study examines the role of social media X in developing Gen Z's writing creativity through the phenomenon of the Alternate Universe (AU) as a form of digital literature in the era of literary digitalization. The research uses qualitative, data collection through observation, interviews, and document studies of AU writers and readers  on social media X. The results of the study show that social media X functions as an interactive digital space that encourages writers to express ideas flexibly through thread, retweet, like, comments, and supporting visual media. Two-way interaction between writers and readers creates a participatory digital literary ecosystem, where readers provide feedback that enriches the creative process. In addition, the use of # (hashtag) and communities such as #AUrecommendation and Local AU Base makes it easier to promote and expand the reach of works. This research confirms that social media X is not only a place for distribution, but also a forum for learning and developing creativity as well as a digital literary community for Gen Z in facing the challenges of literacy culture in the modern era.